Impact of the Extent of Intraventricular Hemorrhage on Functional Outcome in Spontaneous Intracerebral Hemorrhage - Tapu, Shagor Deb; Md. Hassanuzzaman; Touhidur Rahman; Zaman Ahammed; Riyadh Muhammad Marzuk; Suman Sen; Md. Mubinul Huq Chowdhury; Aditi Das; Samee M Adnan; Kamrul Hassan (Bangladesh Journal of Neuroscience, 2026)
Background: The impact of the extent of Intraventricular hemorrhage (IVH) on functional outcomes in patients with Spontaneous intracerebral hemorrhage (sICH) needs to be better established. This study estimated the extent of IVH by the Grabe score (a valid and reliable semiquantitative score to measure IVH volume) in patients with sICH. Objective: It explored the impact of the magnitude of IVH on functional outcomes after one month of stroke onset. Methods: This study prospectively analyzed 104 patients of sICH from the Department of Neurology and Neurosurgery of Chattogram Medical College Hospital from July 2021 to June 2022. The primary outcome was defined as a functional outcome one month after ICH, assessed using the modified Rankin Scale (MRS) dichotomized into favorable (MRS = 0–3) and unfavorable outcome (MRS = 4–6). Secondary outcomes included mortality at one month and a Graeb score-based threshold analysis for the association of the extent of IVH with unfavorable clinical outcomes. Results: The mean age was 60.9±13.6 years, 51% were male, and in 91.3% of the cases, the hematoma was supratentorial. The mortality rate was 39.4%, and 19.2% had a good functional outcome. The Graeb score had a significant positive correlation with the 30-day mRS score (p <0.001, Pearson correlation coefficient = 0.344). Graeb score was good for discriminating 30-day poor functional outcomes with having an area under the ROC curve of 0.699 (95% CI:0.0.572-.0826; P=0.006)]. The risk of having a poor one-month functional outcome was 1.32 times higher in patients with Graeb scores 5-12 than those with Graeb scores 0-4 (RR: 1.32, 95% CI:(1.17-1.50). Admission Graeb score was an independent predictor of 30-day mortality (OR: 1.28; 95% CI:1.06-1.54, p=0.011). Conclusion: As large amounts of IVH (Graeb score e”5) is associated with unfavorable outcome or death after sICH, medical caregivers could use this score in making decisions regarding the use of care resources and other medical care.